Pyridoxine-Dependent Seizures and Intelligence - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1996)
Clinical manifestations, MRI abnormalities, learning disabilities, and effect of pyridoxine dose on intelligence quotients were studied in 6 definite and 3 possible cases of pyridoxine dependent seizures in children, ages 2.5 to 14 years, seen at Newcastle General Hospital, Newcastle upon Tyne, UK.